An Eclectic Analysis of Transitivity andTextual Patterns of Donald Trump’s Inaugural Speech(2017) - Mohammed Sayed (Beni-Suef University International Journal of Humanities and Social Sciences, 2023)
The current study examines the discourse implied in Trump’s political speech in 2017, in accordance with Halliday’s (2014) Systemic Functional Linguistics (SFL). Furthermore, it discovers how Trump constructs discourse according to the Textual Patterns proposed by Hoey (1983). The study follows a qualitative -descriptive approach. Data is collected from Trump’s inaugural speech. The study concludes that the existence of these implicit patterns helps to understand the underlying ideology of Trump’s messages in the interpretation of the discourse which he uses to frame it.The current study examines the discourse implied in Trump’s political speech in 2017, in accordance with Halliday’s (2014) Systemic Functional Linguistics (SFL). Furthermore, it discovers how Trump constructs discourse according to the Textual Patterns proposed by Hoey (1983). The study follows a qualitative -descriptive approach. Data is collected from Trump’s inaugural speech. The study concludes that the existence of these implicit patterns helps to understand the underlying ideology of Trump’s messages in the interpretation of the discourse which he uses to frame it.